The Influence of Family Economic Education, Income, and Lifestyle on the Financial Management Behavior of Housewives in Balesono Village - Elen Berliana Firdaus; RR. Forijati; Efa Wahyu Prastyaningtyas (Universitas Negeri Semarang, 2025)
This study examines the influence of Family Economic Education, Income, and Lifestyle on the Financial Management Behavior of Housewives in Balesono Village, Ngunut, Tulungagung. The population was about 940 housewives, with a sample of 280 randomly selected respondents (Slovin formula, α=5%). Using associative correlation quantitative methods and data analysis with SPSS 23.0, it was found that: (1) Family Economic Education had a significant effect; (2) Income has a significant impact; (3) Lifestyle has a significant effect; (4) The three variables (Family Economic Education, Income, Lifestyle) simultaneously have a significant effect on the Financial Management Behavior of Housewives in Balesono Village.